E EFEKTIVITAS MEDIA LABORATORIUM VIRTUAL PADA PEMBELAJARAN FISIKA DI ERA PANDEMI COVID-19 TERHADAP KETERAMPILAN PROSES SAINS SISWA - Indihartati, Sri (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2022)
The online learning system provides its own challenges where schools and teachers must continue to optimize learning activities in order to remain effective and efficient. This study aims to examine the effectiveness of virtual laboratory media in physics learning in the Covid-19 pandemic era on students' science process skills. The sample in this study was obtained by using a cluster random sampling technique from a population of all students of SMA N 2 Ungaran, namely class XI MIPA 1 as the experimental class and XI MIPA 2 as the control class. The research method used a pretest-posttest control group design, while the data analysis used parametric statistical tests, namely N-gain, independent sample t-test, and paired sample t-test. The gain normality test showed that the average post-test results increased by 0.53 with moderate criteria in the experimental class and 0.28 in the control class with low criteria. The results of the independent sample t-test showed that there was a significant difference in the scientific process skills of the experimental and control groups, namely t count 8.231, greater than t critical 2.042 with a significance level of 5%. In the paired-sample t-test, the value of sig. (2-tailed) of 0.000 < 0.05, it can be concluded that the use of virtual laboratory media in physics learning is effective in improving students' science process skills in the Covid-19 pandemic era.